Analisis dan Perancangan Sistem Informasi Akademik dan Keuangan TK Tunas Bangsa - Sulthan Adam Hanansyah; Welly Purnomo; Kariyoto Kariyoto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The design of Academic and Financial Information System at Tunas Bangsa Kindegarten serves to facilitate guardians in obtaining academic and non-academic information. It also makes it easy for kindergartens to be able to process academic data, record cash flow, and provide information. This design uses the SDLC - Waterfall method with 3 phases, requirements analysis, design, and evaluation. At the requirements analysis phase, the results are business processes, feature identification, actor identification, user requirements, system requirements, and use cases. At the design phase, the results are Activity Diagram, Class Analysis, Sequence Diagram, Class Diagram, Logical Data Model, Physical Data Model, and interface design. In the evaluation phase using the Traceability Matrix, it can be concluded that all user requirements are well-defined and that there are no undefined user requirements. In the evaluation using SUS get 81 results which means the system can be accepted by the user by usability. The suggestion for TK Tunas Bangsa is to continue this research to the development stage. Then when the system is finished, it is better to do maintenance every few times so that the system have no problems.